Sleep quality and sleep hygiene practices among the undergraduate and post graduate medical students in a medical college and tertiary hospital, Navi Mumbai: a cross-sectional study - R., Surekha Aishwarya; Pinto, Violet; Joshi, Sumedha; Mohokar, Anupriya; Singh, Taneya (International Journal Of Community Medicine And Public Health, 2026)
Background: Sleep is vital for physical and mental health, yet medical students are prone to poor sleep due to academic stress and irregular schedules. Poor sleep quality and hygiene negatively impact learning, mood, and well-being. Methods: A cross-sectional study was conducted among 382 medical students at a tertiary medical college in Navi Mumbai, India. Data were collected using a self-administered Google form containing the Pittsburgh sleep quality index (PSQI), sleep hygiene index (SHI), and questions on sociodemographic and lifestyle factors. Statistical analysis was performed using Jamovi version 2.6, applying the Chi-square test and binomial logistic regression to determine associations and predictors. Results: Poor sleep quality was reported by 56.5% of participants, while 53.9% exhibited poor sleep hygiene. Satisfaction with academic performance, family history of sleep disorders, headaches, self-medication, comorbidities, strained relationships, physical activity and number of rooms at the place of stay were significantly associated with poor sleep quality (p<0.05). Factors significantly associated with poor sleep hygiene were accommodation, academic satisfaction, family history of sleep disorders, headaches, self-medication, strained relationships, and weekend screen time (p<0.05). Logistic regression showed students with poor sleep hygiene were nearly twice as likely to have poor sleep quality (OR 1.5-2.5, p<0.05). Conclusions: Poor sleep quality and hygiene are highly prevalent among medical students. Interventions targeting stress management, time regulation, and healthy sleep habits are essential.